Self-Management and Use of Learning Resources in Determining Student Learning Outcomes in Economic Statistics Management Class III An Nuur University - Sri Martono; Winarsih (LPPM Universitas An Nuur, 2022)
Background: Less than optimal student learning outcomes are a separate problem in learning activities on campus. Factors that can be an influence in a student's learning outcomes are self-management and the use of learning resources. Purpose: This study aims to obtain valid evidence on how self-management and the use of learning resources in improving student learning outcomes for the Economic Statistics course for Management class III. Methods: This research is a quantitative type with the research subjects being all students of Management class III An Nuur University. The population was 21 people and the instrument in this study consisted of a questionnaire which included 10 aspects of selfmanagement and 10 aspects of the use of learning resources. Conclusion: From this research, it can be concluded that the self-management factor and the use of learning resources have a significant influence on the learning outcomes of Management Class III students for the Economic Statistics course in the Management Study Program at An Nuur University. Suggestion: The results of this study are expected to be a reference in relation to efforts to improve student learning outcomes.